Dynamical properties of polaritons in semiconductor microcavities (2005)
The main aim of the present thesis work is to study the fundamental features of the different relaxation process for polaritons, when the semiconductor micro-cavity is excited by a non-resonantlaser pump. Our numerical simulations of polariton relaxation, clearly demonstrate that, for the experimental situation, the electron-polariton relaxation mechanism is the most efficient, contrary to the recent published theoretical work and confirming the experimental results. In the present work, the polariton-polariton scattering is inefficient due to the low excitation densities.